TEACHER'S STRATEGY IN IMPROVING STUDENTS' ABILITY TO MEMORIZE THE QURAN AT MADRASAH ALIYAH YAPI SIPARE-PARE, AIR PUTIH DISTRICT - Chairuddin Siregar; Rina Sabrina (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
This type of research is a type of qualitative research. Qualitative research is a type of research whose findings are not obtained through statistical procedures or other forms of calculation and aims to reveal phenomena holistically-contextually through collecting data from natural settings by utilizing the researcher himself as the key instrument.The strategy carried out by the Tahfidz Teacher at the Yapi Sipare-pare Private Madrasah Aliyah in improving the students' ability to memorize the Koran, consists ofof several actions, Private Yapi Sipare-pare in an effort to improve memorization skillsstudents' Koran, namely as follows: 1), there are students who have not been able to read the Koran properly, 2), the teacher's health can interfere with concentration in teaching, 3), there is a feeling of laziness from students when memorizing the Koran, and 4) there is intelligence different from students.The solution to this obstacle can be overcome by the teacher by providing tahsin guidance which is carried out periodically. In addition to the presence of several students who have not been able to read the Koran properly, there are also students who are lazy to memorize. This situation does not occur every day, but when students feel lazy, it will be difficult for students to memorize, even for teachers to guide student memorization. The solution that teachers can do to prevent students from feeling lazy is to always provide motivation in the form of advice and continuous memorization targets so that student memorization is always measurable. In addition to these obstacles there are also obstacles that in practice are not in accordance with the theory presented by the author.